Religious Character Formation Through Islamic Education Learning in Elementary Schools: Evidence from SD Negeri 1 Kameloh Baru - Ristiani Arnila; Asmawati Asmawati; Abdullah Abdullah (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
This study was motivated by the limited internalization of religious values in Islamic Religious Education (IRE) instruction in elementary schools, which tends to emphasize cognitive achievement rather than the development of students’ religious character. The study aimed to describe the implementation of IRE instruction in developing students’ religious character and to identify the supporting and inhibiting factors affecting the process. This study employed a descriptive qualitative approach at SD Negeri 1 Kameloh Baru. Data were collected through participatory observation, in-depth interviews with six informants consisting of the principal, one Islamic Education teacher, one fifth-grade homeroom teacher, and three fifth-grade students, as well as documentation analysis of lesson plans and school religious programs. Data analysis was conducted through data reduction, data display, and conclusion drawing using source and method triangulation to ensure data validity. The findings reveal that religious character development is effectively strengthened through the integration of affective learning objectives, structured religious habituation, teacher role modeling, and a consistent school religious culture. Students demonstrated observable behavioral changes, including increased discipline in prayer, spontaneous greeting habits, peer-supported reminders in worship practices, and the internalization of religious routines as personal awareness rather than formal obligation. The study also found that the effectiveness of religious character formation emerges from the systematic alignment between instructional objectives, repeated religious practices, exemplary teacher behavior, and the institutionalization of religious values within the school environment.